Nickel‐Catalyzed Intermolecular Asymmetric Addition of Aryl Iodides across Aldehydes. (23rd February 2022) - Zhu, Ziqi; Xiao, Jieshuai; Li, Mingjie; Shi, Zhuangzhi
Abstract: Enantioenriched alcohols comprise much of the framework of organic molecules. Here, we first report that chiral nickel complexes can catalyze the intermolecular enantioselective addition of aryl iodides across aldehydes to provide diverse optically active secondary alcohols using zinc metal as the reducing agent. This method shows a broad substrate scope under mild reaction conditions and precludes the traditional strategy through the pre‐generation of organometallic reagents. Mechanistic studies indicate that an in situ formed arylnickel, instead of an arylzinc, adds efficiently to aldehydes, forming a new C−C bond and a chiral nickel alkoxide that may be turned over by zinc powder. Abstract : An enantioselective aryl‐addition has been accomplished using a combination of aryl iodides and aldehydes via asymmetric nickel catalysis. These mild catalytic conditions provide a new strategy for the enantioselective construction of secondary alcohols, avoiding the use of organometallic nucleophiles.